Collaborative Geospatial Infrastructure: A Coordinative Approach in Disaster Management - Santosa, Purnama Budi (2006)
Geospatial data (i.e. maps depicting geo-referenced locations) are important in disaster management might be undeniable. Geospatial information is essentially required for both disaster prevention and preparedness. However, to what extent geospatial information has been effectively utilized remains a question. Geospatial data may be available but there is usually no coordination in their utilization. Further more, it has been observed in Indonesia that infrastructure of geospatial resources at national and local levels are inaccessible. Consequently, parties concerned with disaster management initiate their own efforts on data collection, access, and dissemination in a sporadic way. In absence of a geospatial infrastructure, responsible agencies lack integrated decision supports to process incoming data and information into sound knowledge for actions. These phenomena motivate a research toward the development of a collaborative geospatial infrastructure. The philosophy behind this research is how to establish a system that is accessible by parties concerned in disaster management in order to enhance coordination. Being in the early stage, this paper will further elaborate conceptual design of the said research. Design of research will be given including steps, collaborators involved, and the expected outcomes. This research is part of Hi-Link project in Gadjah Mada University, funded by JICA.